Anlotinib inhibits cervical cancer cell proliferation and invasion by suppressing cytokine secretion in activated cancer-associated fibroblasts - Xiong, Yaozu; Xu, Xiaoting; Zhou, Xilei; Tong, Yusuo; Yu, Changhua (Frontiers in Oncology, 2024)
Objective:The aim of this study was to investigate whether anlotinib could exert an inhibitory effect on the proliferation and invasion of cervical cancer cells by inhibiting cytokines secreted by activated cancer-associated fibroblasts (CAFs).Methods:CAFs were isolated from cervical cancer tissues and experimentally studied in vivo and in vitro. Molecular biology experimental methods were used to verify whether anlotinib could inhibit the pro-carcinogenic effects of CAFs derived from cervical cancer tissues.Results:CAFs promote the proliferation and invasion of cervical cancer cells.CAFs and suppressed the release of interleukin (IL)-6 (IL-6) and IL-8. In vivo studies have shown that anlotinib diminished the growth of xenografted cervical cancer cells, and treatment in combination with docetaxel had an even more significant tumor growth inhibitory effect.Conclusions:Anlotinib inhibits the pro-cancer effects of CAFs by suppressing the activation of CAFs and the secretion of pro-cancer cytokines. Our findings suggest that the combination of anlotinib and docetaxel may be a potential strategy for the treatment of refractory cervical cancer.